Review on Utilization of Visual Basic Software for Improving Students’ Computer Programming Performances - Gatchalian, Chuckee B.; Handig, Joy Edilaine R.; Baluyot, Fioglo (ASEAN Journal of Educational Research and Technology, 2024)
The main objective of this study is to review on utilization of visual basic software for improving students’ computer ability. This study is a literature survey. We focused on two aspects: (i) utilization of visual basic software and (ii) computer programming performance. This study provided important information and benefits to the school, administrators, teachers, students, and researchers.